(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2016)
This paper tries to explore the many ethical, social and legal issues surrounding surrogacy, focusing in particular on the implications concerning the interest of the minor involved, respect of women’s dignity and the evolving definition of parenthood.